2004
DOI: 10.1038/sj.leu.2403351
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginase pharmacodynamics differ by formulation among children with newly diagnosed acute lymphoblastic leukemia

Abstract: Polyethylene glycol-conjugated (PEG) asparaginase is approved for use in patients who develop allergy to other forms of asparaginase, although its ability to deplete asparagine systemically in patients with hypersensitivity has not been well elucidated. In 53 children with newly diagnosed acute lymphoblastic leukemia, we serially assessed asparagine concentrations in cerebrospinal fluid (CSF) and plasma as well as serum anti-asparaginase antibodies. All patients received native Escherichia coli (Elspar) aspara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 23 publications
(24 reference statements)
1
37
0
2
Order By: Relevance
“…on April 27, 2019. by guest www.bloodjournal.org From reported that the administration of pegylated E coli ASE, compared with native E coli ASE or Erwinia ASE, after an allergic reaction to native E coli ASE or in case of detectable Abs against the native form did not increase the depletion of asparagine. 22 In addition, Asselin et al 23 determined an increased clearance of pegylated E coli ASE after allergic reactions to native E coli ASE. However, drug monitoring within the ALL-BFM trials provided evidence of sufficient ASE activity in numerous patients when pegylated E coli ASE was given as a second-line treatment after allergic reactions to E coli ASE.…”
Section: Monitoring Of Anti-e Coli Asparaginase Antibodies 5779mentioning
confidence: 99%
“…on April 27, 2019. by guest www.bloodjournal.org From reported that the administration of pegylated E coli ASE, compared with native E coli ASE or Erwinia ASE, after an allergic reaction to native E coli ASE or in case of detectable Abs against the native form did not increase the depletion of asparagine. 22 In addition, Asselin et al 23 determined an increased clearance of pegylated E coli ASE after allergic reactions to native E coli ASE. However, drug monitoring within the ALL-BFM trials provided evidence of sufficient ASE activity in numerous patients when pegylated E coli ASE was given as a second-line treatment after allergic reactions to E coli ASE.…”
Section: Monitoring Of Anti-e Coli Asparaginase Antibodies 5779mentioning
confidence: 99%
“…Why this happens is not well understood. Florid hypersensitivity reactions can occur, necessitating withdrawal of the drug, though not all patients with hypersensitivity develop neutralizing antibodies and not all patients who develop neutralizing antibodies exhibit hypersensitivity (12,13). Again, the reason why some patients develop allergy to l-asparaginase remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One protein that falls into this category is L-asparaginase (ASNase), an enzyme that is used for treating acute lymphoblastic leukaemia. This protein was one of the first to be modified with mPEG because of its propensity to cause severe hypersensitivity reactions (up to 20-30% of patients) 13 or suffer from 'silent inactivation' by the neutralizing or opsonizing antibodies 14,15 . Modification of ASNase with mPEG in part overcomes these problems 16 , however, a key problem is that antibody responses against mPEG-ASNase continue to occur in B18% of patients [17][18][19] .…”
mentioning
confidence: 99%